Assessing community attitudes toward industrial heritage tourism development. Issue 3 (3rd May 2020) - Xie, Philip Feifan; Lee, Maria Younghee; Wong, Jose Weng-Chou
ABSTRACT: Tourism can have both positive and negative outcomes for residents in communities where sharing and preserving industrial heritage may be viewed as conflicting goals. The aim of this study is to ascertain residents' attitudes toward the redevelopment of the defunct shipyard located in Coloane, Macau. The grounded theory approach is employed to elicit residents' perceptions of tourism projects proposed by local government. The findings reveal that residents' rights, co-creation, NIMBY (Not In My Back Yard), place attachment and authenticity are major concerns for the redevelopment. This study suggests that residents' perceptions and attitudes toward tourism development play a key role in shaping urban revitalization.